Value-Based Health Education Interventions and PHBS Change: A Qualitative Study - Dian Meiliani Yulis (Jurnal Edukasi Ilmiah Kesehatan, 2026)
Introduction: Clean and Healthy Living Behavior (PHBS) is a fundamental component of public health promotion aimed at preventing environmentally related diseases. In Kecamatan Baguala, Ambon, the inconsistent implementation of PHBS indicates a gap between knowledge, attitudes, and actual practices. This study aimed to analyze the effectiveness of value-based health education interventions in improving PHBS among community members. Methods: A qualitative descriptive design was employed from August 2024 to January 2025. Participants were selected using purposive sampling, including health cadres, community leaders, homemakers, and general residents. Data were collected through in-depth interviews, participant observation, focus group discussions, and document analysis. Thematic analysis was conducted using data reduction, data display, and conclusion verification procedures. Triangulation ensured credibility and data saturation. Results: Findings revealed that baseline PHBS knowledge was superficial, attitudes were generally positive but inconsistently practised, and behavioral implementation was influenced by cultural habits and structural limitations. The value-based intervention enhanced awareness, strengthened intrinsic motivation, and promoted gradual behavioural improvements in handwashing, sanitation, and household hygiene management. Conclusion: Value-based health education effectively improved cognitive, motivational, and social dimensions of PHBS. Sustainable implementation, however, requires integrated support involving infrastructure, community engagement, and policy reinforcement